Broadband radar absorbing composites: Spatial scale effect and environmental adaptability. (8th September 2020) - Zhang, Zhong; Wang, Changxian; Yang, Haiyang; Wang, Panding; Chen, Mingji; Lei, Hongshuai; Fang, Daining
Abstract: Radar absorbing structures with multiple resistive frequency selective surfaces (FSSs) are of great potential in the aerospace and marine fields. However, reliable theoretical prediction models of multilayer circuit-analog (CA) absorbers together with proper optimizing programs have not yet well been established despite the large number of reported investigations. Herein, a precise and comprehensive optimization method was proposed for the design of lightweight and broadband absorbing structures based on improved genetic algorithm. To this end, the spatial scale effect of the entire structures and interlayer interference effects between FSS films were firstly considered. Several absorbing sandwich structures composed of fiber-reinforced epoxy facesheets, polyvinyl chloride (PVC) foam and FSS films with square patterns of various periods were then fabricated. The environmental adaptabilities of the as-obtained absorbing structures were assessed through electromagnetic and load-bearing experimental tests under different ambient temperatures and marine corrosion durations. The optimized absorbing sandwich structures displayed ultra-broadband absorbing capabilities from 2 to 17 GHz and average bending strength of 80 MPa. The influence of ambient temperature on absorbing capability was slight due to the thermostability of carbon conductive ink. In addition, degeneration effect of marine corrosion on the absorbing capability was initially severe but tended to stabilize as corrosion process proceeded. The results of this study provide a useful guideline for the design of integrated multi-functional absorbing composite structures for actual applications. Highlights: Precise genetic algorithm for optimizing program in view of scaling effect is proposed. Interlayer interference between FSS films is analyzed at different polarization modes. Environmental adaptabilities of proposed absorbing composites are investigated.